176k views
0 votes
Which statement about the binomial expansion of (x2 – x)9 is true?

The first term is –x18.

The second term is 9x17.

The third term is 36x14.

The last term is –x9.

User Moha
by
4.8k points

2 Answers

2 votes

Answer:

D

Explanation:

just took it

User Sam Van Beastlo
by
5.3k points
5 votes

Answer:

Option D.

Explanation:

The given expression is


(x^2-x)^9

Here, n=9, p=x^2 adn q=-x.

kth term in the binomial expansion of
(p+q)^n is


T_(r)=^nC_(r-1)p^(n-r+1)q^(r-1)

First term of the binomial expansion of
(x^2-x)^9 is


T_(1)=^9C_(1-1)(x^2)^(9-1+1)(-x)^(1-1)=x^(18)

Second term of the binomial expansion of
(x^2-x)^9 is


T_(2)=^9C_(2-1)(x^2)^(9-2+1)(-x)^(2-1)=9(x^16)(-x)=-9x^(17)

Third term of the binomial expansion of
(x^2-x)^9 is


T_(3)=^9C_(3-1)(x^2)^(9-3+1)(-x)^(3-1)=9(x^14)(x^2)=36x^(16)

Last or 10th term of the binomial expansion of
(x^2-x)^9 is


T_(10)=^9C_(10-1)(x^2)^(9-10+1)(-x)^(10-1)=1(x^0)(-x^9)=-x^(9)

Therefore, the correct option is D.

User Tony Stark
by
5.4k points